Revision of the stick insect genus Clitarchus Stål (Phasmatodea: Phasmatidae): new synonymies and two new species from northern New Zealand - Buckley, Thomas R.; Myers, Shelley S.; Bradler, Sven (Zootaxa, 2014)
We describe two new species of Clitarchus Stål from Northland, New Zealand. Clitarchus rakauwhakanekeneke sp. nov. is described from the Poor Knights Islands and Clitarchus tepaki sp. nov. is described from the Te Paki / North Cape area and the Karikari Peninsula at the northernmost tip of New Zealand. Two new synonymies are proposed including Clitarchus multidentatus Brunner (syn. nov.) and Clitarchus tuberculatus Salmon (syn. nov.) as synonyms of Clitarchus hookeri (White). Clitarchus magnus Brunner, recorded from Thailand, is transferred to Ramulus Saussure and given the replacement name Ramulus changmaiense nom. nov. The holotype of C. multidentatus was recorded as being collected from New Caledonia; however we believe this is a labelling error and the specimen was collected from New Zealand. These taxonomic changes render Clitarchus endemic to New Zealand and consisting of three species; C. hookeri, C. rakauwhakanekeneke and C. tepaki. Keys to the adult males and females of Clitarchus species are given in addition to notes on host plants, ecology and geographic distributions.